Urine-based point-of-care testing for factor-Xa-inhibitors in acute ischemic stroke patients: a feasibility study - Doeppner, Thorsten R.; Olbricht, Linus; Maxhuni, Toska; Alhaj Omar, Omar; Sachs, Ulrich J.; Juenemann, Martin B.; Huttner, Hagen B.; Gerner, Stefan T. (Frontiers in Neurology, 2023)
Introduction Direct oral anticoagulants (DOACs) have become widely used in clinical practice for preventing thromboembolic events. Point-of-care testing methods, particularly those based on urine samples, offer a promising approach for rapid and accurate assessment of DOAC presence. This pilot study aims to evaluate the utility of a urine-based DOAC dipstick test as a point-of-care tool for identifying DOAB presence in acute ischemic stroke (AIS) or transient ischemic attack (TIA) patients. Patients and methods This prospective pilot study included patients with AIS/TIA eligible for DOAC-measurement. After exclusion of 3 patients, 23 patients with DOAC-intake (DOAC group; factor-Xa-inhibitors; n = 23) and 21 patients without DOAC-intake (control-group) remained for analyses. The urine-based DOAC dipstick test and parallel blood-based specific DOAC-level assessment were performed in all patients. Time-intervals of sampling urine/blood sampling and result of DOAC-test were recorded to analyze a potential time benefit based on dipstick evaluation. Results The urine-based DOAC dipstick test demonstrated high sensitivity (100%) and specificity (100%), correctly identifying all patients with anticoagulatory activity due to DOAC intake (i.e., anti-Xalevel ≥30 ng/mL). Moreover, the visual readout of the test provided semiquantitative information on drug-specific anti-Xa levels, showing a sensitivity of 83% and specificity of 93% to detect anti-Xa levels ≥120 ng/mL. The dipstick test exhibited a median time-benefit of 2:25 h compared to standard blood-based DOAC-level testing. Discussion The results of this pilot study underline the efficacy of urine-based point-of-care testing as a rapid and reliable method for assessing DOAC presence in patients with acute ischemic stroke. Conclusion The value of this tool for clinical decision-making in stroke management needs to be established in future trials. Clinical Trial Registration: Clinicaltrails.org identifier [NCT06037200].